Assessment of Agro-Waste Potentials for the Generation of Electrical Energy in Northeast Nigeria - Bukar, A.; Mustapha, K.; Aliyu, U. O.; Jiya, J. D.; Bakare, G. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
In this paper eight major Agricultural-wastes (agro-waste) (maize cob, groundnut shell, bean pod, wheat husk, rice husk, millet bran, sorghum bran and sugar cane bagasse) derived from widely grown crops in the northeast sub-region have been investigated for their energy resource potentials. The core research task is to estimate the aggregate crop residues from raw data collected from river basin authorities and ministries of agriculture and water resources as well as from structured surveys of major markets, large commercial farms and Agro-Allied Industries. This work relies on directed data analytics approach and has arrived at gross estimates of 6.89x104 metric tons per annum as agro-wastes available for electricity production; corresponding to approximately 13.5% share of the total agro-wastes of the northeast sub-region. Further, samples of all agro-wastes were characterized via proximate analysis which yielded their respective lower heating values to be within the range of 12.52MJ/kg to 16.66MJ/kg. From end-use viewpoint, the estimated agro-wastes of the study area can generate electrical energy of 55.8GWh/annum for geographically scattered rural communities.